Design of EMI and suppression structure based on bar-via. (June 2021) - Li, Na; Miao, Min
Abstract: Through-vias may radiate electromagnetic waves propagating in the substrate of 2.5D integration interposers under the excitation of high-frequency and high-speed signals carried by vias, thus inducing parasitic interference and edge radiation. In order to suppress electromagnetic interference (EMI) between through-silicon vias (TSV) on the silicon interposer, a 6G-B-TSV (Bar TSV) circular cage shield structure is proposed. Its shielding effect is superior to the unshielded structure and the traditional cylindrical TSV grounded shielding structure. In order to suppress EMI between the two cross-layer signal channels on the organic interposer, a 6G-B-Via shielding structure and a shielding fence structure consisting of single-row grounded B-Vias are proposed. Other, a design with B-Via fence on the edge of the substrate to suppress edge radiation is further proposed. The comparison of the simulation results shows the superiority of the design in shielding and suppression effect. Finally, the actual test results of samples verify the effectiveness of the structural designs and simulation schemes.